Pathogenesis and Treatment of Neurologic Diseases Associated With Mycoplasma pneumoniae Infection - D’Alonzo, Renato; Mencaroni, Elisabetta; Di Genova, Lorenza; Laino, Daniela; Principi, Nicola; Esposito, Susanna (Frontiers in Microbiology, 2018)
Mycoplasma pneumoniae is mainly recognized as a respiratory pathogen, although it is associated with the development of several extra-respiratory conditions in a great number of cases. Diseases affecting the nervous system, both the peripheral (PNS) and the central nervous system (CNS), are the most common. In some cases, particularly those that involve the CNS, M. pneumoniae -related neuropathies can have a severe clinical course and lead to death or to persistent neurologic problems with a significant impact on health and a non-marginal reduction in the quality of life of the patients. However, the pathogenesis of most of the M. pneumoniae -related neuropathies remains undefined. The main aim of this paper is to discuss what is presently known regarding the pathogenesis and treatment of the most common neurologic disorders associated with M. pneumoniae infection. Unfortunately, the lack of knowledge of the true pathogenesis of most of the cases of M. pneumoniae-mediated neurological diseases explains why treatment is not precisely defined. However, antibiotic treatment with drugs that are active against M. pneumoniae and able to pass the blood-brain barrier is recommended, even though the best drug, dosage, and duration of therapy have not been established. Sporadic clinical reports seem to indicate that because immunity plays a relevant role in the severity of the condition and outcome, attempts to reduce the immune response can be useful. However, further studies are needed before the problem of the best therapy for M. pneumoniae -mediated neurological diseases can be efficiently solved.